Understanding the enhancement of CaO on water gas shift reaction for H2 production by density functional theory. (1st November 2021) - Yan, Xianyao; Li, Yingjie; Zhang, Chunxiao; Wang, Yuzhuo; Zhao, Jianli; Wang, Zeyan
Highlights: The WGS reaction mechanism in the presence of CaO was studied by DFT calculations. The most possible pathway of WGS reaction on the CaO surface is the redox-a pathway. As the rate-limiting step, H2 O is dissociated spontaneously on the CaO surface. The presence of CaO decreases energy barrier of WGS reaction along redox-a pathway. Abstract: The water gas shift reaction is an important reaction for H2 production in various industrial applications. The presence of CaO can promote the reactivity of the water gas shift reaction without any catalysts, but the enhancement mechanism of CaO in this reaction is difficult to determine just by the experiment. In this work, the water gas shift reaction along four possible pathways on the CaO surface were studied by density functional theory (DFT) analysis. The energy barriers along the pathways were analyzed to determine the most possible reaction pathway and role of the CaO surface. The DFT calculation results show that the WGS reaction is more prone to proceed along the redox-a pathway probably: H2 O dissociates into hydroxyl and atomic H spontaneously when H2 O and CO co-adsorb on the CaO surface, then the hydroxyl continues to dissociate and CO is oxidized by the generated atomic O. Afterwards, H2 molecule generates from two atomic H, and then CO2 adsorbs and H2 desorbs simultaneously on the CaO surface. The CaO surface enables the spontaneous dissociation of H2 O, which is the rate-limiting step of WGS reaction. The generation of CO2 is facilitated, and the energy barrier is reduced from 2.304 to 0.757 eV on the CaO surface. Besides, the formation of CO3 2− on the surface avoids the energy barrier for CO2 desorption, while the CO2 also occupies the active site and reduces the enhancement of CaO on WGS reaction. The calculation result reinforces the comprehension on the mechanism of CaO on WGS reaction.